Harpactea azowensis (Araneae, Dysderidae) из заповедника Аскания-Нова - Гурьянова, В.E. (Вестник зоологии, 1993)
A redescription of Harpactea azowensis Charitonow, 1956 based on material collected in Ascania-Nova Nature Reserve and deposited in the author’s collection (Institute of Zoology, Ukrainian Academy of Sciences (Kiev).